Peran Gaya Kepemimpinan Visioner Kepala Sekolah Dalam Pencegahan Tindak Korupsi di Sekolah Menengah Pertama - Satrio Devan Nugroho; Ilham Fahmi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Corruption is a crime that often occurs in almost all institutions. In this study a case study of junior high schools, crimes like this can be prevented by having a leader who has a visionary nature, because it can provide crime prevention in the scope of education, especially junior high schools, because this pattern is able to give meaning to the work and effort that is done. needs to be carried out jointly by members of the organization by giving direction and meaning to the work and efforts carried out based on a clear vision. This research uses descriptive qualitative method with a focus on literature study. The role of the principal who has a visionary leadership style model in preventing corruption can be done by applying various types of strategies, namely: preventive strategies, detective strategies, and repressive strategies.